Peramalan Prakiraan Cuaca Setiap Hari di Kota Medan dengan Pendekataan Rantai Markov - Septia Cahaya Sari Sipayung; Thanaya Lovry Lastiar; Trinita Melyana Hutagalung; Sisti Nadia Amalia (International Forum of Researchers and Lecturers, 2024)
This research utilizes the Markov Chain method to analyze daily weather data in the city of Medan. The main objective of this study is to forecast weather changes in the future based on the weather conditions of the previous day. Daily weather data was collected from the nearest weather station over a specific period of time. The analysis results indicate that the Markov Chain model provides good estimates of the likelihood of weather changes from one day to the next. The steady state probabilities demonstrate the dominance of partly cloudy and clear weather in the long term. This research provides valuable insights for various sectors related to weather, such as agriculture, transportation, and tourism.